Analisis Perbandingan Rasio Roa dan NPL antara Bank Konvensional dan Bank Syariah (Studi pada PT. Bank Mega Tbk dan PT. Bank Mega Syariah Tbk) - Khairin, Fibriyani Nur (Mazahib, 2014)
This study aims to determine the differences in the performance of NPLs AND ROA at PT. Bank Mega Tbk and PT. Bank Mega Syariah, Tbk period 2009-2012. This study used a descriptive study using secondary data obtained from the web Stock Exchange and Bank Mega Syariah website. Data analysis method used is the method of time series and cross sectional approach. From these results it is known that the performance of NPLs and ROA at PT. Bank Mega Tbk and PT. Bank Mega Syariah is relatively good. However, from the NPF ratio it is better than its sister company, because NPF Bank Mega Syariah showed a decreasing trend since last seen 3 years of observation compared with NPL Mega Bank continued to increase during the period.